1999
DOI: 10.1111/j.1600-079x.1999.tb00563.x
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal development of circadian melatonin production in domestic chicks

Abstract: In contrast to the situation in mammals, in which circadian melatonin production by the pineal gland does not begin until some time after birth, the development of pineal gland rhythmicity is an embryonic event in the precocial domestic fowl. A distinct melatonin rhythm was found in 19-d-old chick embryos maintained under light:dark (LD) 16:8. No significant variation in melatonin levels was detected in embryos exposed to LD 8:16. The melatonin rhythm in the pineal gland and plasma of chick embryos incubated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
7

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 23 publications
3
47
7
Order By: Relevance
“…According to Ubuka et al (3), GnIH begins its function around the time of hatching and acts as a hypothalamic factor to regulate gonadotropin release in quail. It has also been reported that melatonin synthesis and secretion begin during late-embryonic life in the chicken (30)(31)(32). From the present and previous studies, we suspect that the action of melatonin on GnIH expression begins around the time of hatching, and remains during development and in adulthood.…”
Section: Figmentioning
confidence: 58%
“…According to Ubuka et al (3), GnIH begins its function around the time of hatching and acts as a hypothalamic factor to regulate gonadotropin release in quail. It has also been reported that melatonin synthesis and secretion begin during late-embryonic life in the chicken (30)(31)(32). From the present and previous studies, we suspect that the action of melatonin on GnIH expression begins around the time of hatching, and remains during development and in adulthood.…”
Section: Figmentioning
confidence: 58%
“…It is possible that effect off different wavelengths on the opsins could be the mechanisms or part of the mechanism that is altering physiology during embryogenesis, that has resulted in the observed increases hatchability and decreases fear response and stress susceptibility. We know that light stimulation during incubation alters brain development (Rogers and Krebs, 1996) and hormone levels (Zeman et al, 1999) during development. Both of these have been noted to change behavior (Rogers and Workman, 1989) and physiology (Nelson and Demas, 1997) as well.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, when chicks were exposed to 12L:12D during prehatch Days 13 to 18 and tested during their subjective day, they had shorter tonic-immobility durations than when chicks were tested during their subjective night. This provides evidence that the endogenous clock becomes functional and can respond to light cues late in incubation (Nichelmann, Höchel, & Tzschentke, 1999;Zeman, Gwinner, Herichová, Lamosová, & Kost'ál, 1999).…”
Section: Resultsmentioning
confidence: 91%